Daily urinary sodium and potassium excretion in Chinese first-generation migrants in Italy. (1st July 2019) - Modesti, Pietro Amedeo; Marzotti, Ilaria; Rapi, Stefano; Rogolino, Angela; Cappuccio, Francesco P.; Zhao, Dong; Costanzo, Gianfranco; Galanti, Giorgio; Boddi, Maria
Abstract: Background: China has one of the highest salt intake levels in the world, and Chinese people form one of the largest foreign-born communities now living in Europe. The present study was performed to assess 24-hour urinary sodium and potassium excretion in Chinese migrants in Italy and to explore possible associations with hypertension, hypertension awareness, and length of residence in Italy. Methods: A cross-sectional evaluation was conducted on 319 first-generation Chinese migrants (154 women and 165 men) aged 18–70 years. Subjects were asked to do a 24-hour urine collection and the relationships of urinary sodium and potassium and arterial blood pressure, hypertension (BP ≥ 140/90 mmHg or anti-hypertensive drug use), hypertension awareness, and years of residence in Italy were investigated with linear or logistic regression analysis. Results: Sodium excretion was 145.2 mmol/day (95%CI 138.0–152.3) in men, and 134.7 (95%CI 127.6–141.8) in women corresponding to a dietary salt intake of 9.4 g/day (95%CI 9.0–9.9) and 8.8 (95%CI 8.3–9.2) respectively. Potassium excretion was 35.1 mmol/day (95%CI 33.6–36.5), with no significant difference by gender. At multivariable adjusted linear regression analysis body mass index, low education level, and hypertension were positive predictors of sodium urinary excretion; gender (women), and body mass index were positive predictors of potassium excretion. Sodium and potassium excretion were unaffected by hypertension awareness or years of residence in Italy. Conclusions: Sodium excretion in Chinese workers is higher than recommended and in line with high salt intake in Italy. Potassium consumption remains low. Highlights: Daily sodium excretion of Chinese migrants was in line with the high sodium intake in Italy, while potassium excretion was markedly lower. The area of origin in China remains a proxy for sodium and potassium intake after migration Hypertension awareness is a powerful drive to treatment for Chinese in Italy whereas the importance of salt intake reduction is not appreciated.